Africa: African Agricultural Market Information Network (AFAMIN) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The African Agricultural Market Information Network (AFAMIN) is an Internet-based agricultural market information exchange system linking the international community and West African countries.